Smart Classroom Environment Via IoT in Basic and Secondary Education - EL Mrabet, Hicham; Ait Moussa, Abdelaziz (Transactions on Engineering and Computing Sciences, 2017)
The rapid evolution of information and communication technologies (ICT) has created a new paradigm of the Internet, known as the Internet of Things (IoT), which represents a group of connected objects Using wireless links (WiFi, RF, NFC, Zigbee…)to exchange information between objects and persons. The Internet of Things has changed the way people and objects interact with each other, and education has not been immune to this change, which has created new forms of interaction between teachers and learners that helps improve the teaching and learning process.In the field of education, we can imagine that students use new technologies to carry out projects and educational activities in the classroom. In this research,the focus is on the application of Internet of Things in the Smart Classrooms.This paper presents and discusses the need of integrating the Internet of Things to improve learning at the basic and secondary school, mainly through information and communication technologies (ICT) at its disposal.